(untitled) (Simbiótica. Revista Eletrônica, 2024)
Reflection on the peculiar moment in Brazil, perhaps in the world, caused by the Covid-19 pandemic and the planetary circumstance of confusion, questioning, which lays bare the contradictions and ambivalences between thinking, acting and feeling. This moment has led to a super-presence of extravagant emotions and feelings that leak a historical moment in which the old has not died and the new has not yet been born; attracting new questions implicated in perversion.